3D macroelement approach for nonlinear FE analysis of URM components subjected to in-plane and out-of-plane cyclic loading. (1st October 2020) - Minga, E.; Macorini, L.; Izzuddin, B.A.; Caliò, I.
Highlights: Novel 3D macroelement approach for nonlinear simulation of masonry components. Accurate representation of complex failure modes under cyclic loading. Nonlinear cohesive-frictional interfaces describe the interaction between adjacent deformable blocks. Enhanced kinematics to represent out-of-plane bending response. Model validation via comparison with results from physical experiments. Abstract: The paper presents a novel 3D macroelement approach for efficient and accurate nonlinear analysis of unreinforced masonry components subjected to in-plane and out-of-plane cyclic loading. A macroscopic description for masonry is employed, where macroelements, consisting of deformable blocks interacting through cohesive interfaces, are used to represent large portions of masonry walls, enhancing computational efficiency. Enriched kinematic characteristics are adopted for the homogeneous blocks, where in-plane shear and out-of-plane bending modes are described by two independent Lagrangian parameters. Moreover, a detailed material model for the nonlinear interfaces connecting adjacent elements enables an accurate representation of complex failure modes and cracking patterns in masonry walls. As a result, the proposed FE strategy can be employed for accurate response predictions of large masonry structures subjected to cyclic loading conditions. The accuracy of the macroelement approach is validated through comparisons against results of experimental tests of solid and perforated masonry walls under in-plane and out-of-plane loading.